Work-related ill-health in construction: The importance of scope, ownership and understanding. (December 2019) - Jones, Wendy; Gibb, Alistair; Haslam, Roger; Dainty, Andy
Highlights: Work-related ill-health in construction presents a significant management challenge. Poor knowledge, lack of ownership and a sense of resignation increase the risks. A focus on general wellbeing can distract from the reduction of work-related hazards. Improved access to OH services and management of health data are needed. Abstract: Work-related ill-health in construction is a major concern worldwide, presenting significant risk management challenges. This three-year research project studied a multi-million pound regional construction project and a multi-billion pound infrastructure megaproject in the UK. It used interviews (n = 237) and meeting observations (n = 120) to examine contemporary approaches to managing occupational health in the industry and their limitations. It was found that the conceptualisation of 'health' is a significant issue: activities which focus on the general health and wellbeing of the workforce can distract from the reduction of work-related hazards at source. There are further challenges in the way health risk is perceived and tolerated by workers and organisations. This is partly because of the invisibility and latency of the associated health effects, but also reflects incomplete knowledge and a sense of resignation. Crucially, there is evidence of a lack of ownership of health within organisations and on the part of some managers, frontline workers and OSH professionals. These aspects are exacerbated by the way in which the construction industry operates, with high levels of self-employment and worker mobility; the temporary nature of projects which inevitably foregrounds immediate safety concerns over longer term health issues; and the cost of and limited access to health services. Health risks are challenging to manage because 'health' differs from 'safety'; in terms of the hazards themselves but also in the way that the construction sector understands and manages risk. These differences need to be recognised and addressed to achieve lasting improvements to worker health in construction.